Constructing secondary students’ critical thinking skill test on heat concept - K Mahbubah; D Rusdiana; E A Juanda; N Hermita; I R Hakim; A Samsudin (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
Physics education has been conducting to develop critical thinking skill and need to instrument test to measure students’ critical thinking skill. This study aims to construct secondary students’ critical thinking test (CTS) on heat concept. The instrument test is constructed by Halpern’s critical thinking framework with five domains specific critical thinking. The method which is utilized in this study is 3D+1I (Define, Design, Develop and Implementation) conducted to secondary students who have studied heat concept. The respondents are 30 students of eleventh grade in secondary school. The result of this research was domain specific critical thinking got highest score and the lowest score in domain specific critical thinking was predict the probability event In conclusion, secondary students’ critical thinking test could measure critical thinking of students on heat concept.